Report on the "English Language Section of Varga Tamás Days 2009" (Teaching Mathematics and Computer Science, 2010)
The 9th English Language Section as a part of the Varga Tamás Days was organised by the Department of Mathematics Education at the Teacher Training Institute of the Eötvös Loránd University. We report on the talks and the following discussions in this section.